APLIKASI SPREADSHEET PADA PERANCANGAN RODA GIGI LURUS - Dirga Tangel; Stenly Tangkuman; Hengky Luntungan (JURNAL POROS TEKNIK MESIN UNSRAT, 2016)
A gear is one of the important elements for transferring motion (especially rotation) and power or energy in a transmission system between the driver and the object to be driven. Gear manufacturing is quite complicated and complex with a variety of size and accuracy depends on the role of the gear itself in a machine. The use of speadsheet application provides advantages for designers where the design process becomes easier. Spreadsheet is an interactive computer application program to organize and analize data in tables. This paper presents an application of spreaddsheet that has been made for designing a spur gear. Keywords: design, spur gear, spreadsheet